Characterization of β-Cyclodextrin functionalized rice husk biochar - Rajandran, Prabu; Nasratun, Masngut (AIP Publishing, 2022)
β-cyclodextrin, generated from the enzymatic degradation of starch, has received a lot of attention in removing various contaminates. However, because of its high-water solubility, β-cyclodextrin's use as an adsorbent has been limited. Thus, β-cyclodextrin was attached to the surface of insoluble materials to improve its stability in an aqueous solution. Several types of β-cyclodextrin composites have been studied extensively on a laboratory scale. However, β-cyclodextrin functionalized rice husk biochar (CD-RHB) as an adsorbent is rarely reported. This study aimed to look into the best crosslinker for CD-RHB preparation. Therefore, two different crosslinkers participated in preparing CD-RHB, namely epichlorohydrin, and phosphoric acid. Then, the developed adsorbents (epichlorohydrin-based CD-RHB and phosphoric acid-based CD-RHB) were systematically compared concerning β-cyclodextrin density using scanning electron microscopy (SEM), Fourier-transform infrared (FTIR) spectroscopy, and a thermal analyzer. As observed, β-cyclodextrin was successfully decorated and grafted on both CD-RHBs. For example, SEM observations demonstrated that the pores on the surface of developed adsorbents loaded with β-cyclodextrin. Besides, the TGA results show that the CD-RHBs experience weight loss at the temperature of 76-375 °C (epichlorohydrin-based CD-RHB) and 62-313 °C (phosphoric acid- based CD-RHB), which indicated the decomposition of β-cyclodextrin. However, epichlorohydrin-based CD-RHB shows higher β-cyclodextrin content than phosphoric acid-based CD-RHB on its surface. It is because -OH and C-O-C groups at epichlorohydrin-based CD-RHB show more prominence transmittance. In conclusion, epichlorohydrin is the appropriate crosslinker for the preparation of CD-RHB.